LncRNA MEG3 inhibits the progression of prostate cancer by modulating miR‐9‐5p/QKI‐5 axis. Issue 1 (22nd November 2018) - Wu, Meng; Huang, Yawei; Chen, Tongchang; Wang, Weichao; Yang, Shiguang; Ye, Zhenfeng; Xi, Xiaoqing
Abstract: This study was designed to detecting the influences of lncRNA MEG3 in prostate cancer. Aberrant lncRNAs expression profiles of prostate cancer were screened by microarray analysis. The qRT‐PCR and Western blot were employed to investigating the expression levels of lncRNA MEG3, miR‐9‐5p and QKI‐5 . The luciferase reporter assay was utilized to testifying the interactions relationship among these molecules. Applying CCK‐8 assay, wound healing assay, transwell assay and flow cytometry in turn, the cell proliferation, migration and invasion abilities as well as apoptosis were measured respectively. LncRNA MEG3 was a down‐regulated lncRNA in prostate cancer tissues and cells and could inhibit the expression of miR‐9‐5p, whereas miR‐9‐5p down‐regulated QKI‐5 expression. Overexpressed MEG3 and QKI‐5 could decrease the abilities of proliferation, migration and invasion in prostate cancer cells effectively and increased the apoptosis rate. On the contrary, miR‐9‐5p mimics presented an opposite tendency in prostate cancer cells. Furthermore, MEG3 inhibited tumour growth and up‐regulated expression of QKI‐5 in vivo. LncRNA MEG3 was a down‐regulated lncRNA in prostate cancer and impacted the abilities of cell proliferation, migration and invasion, and cell apoptosis rate, this regulation relied on regulating miR‐9‐5p and its targeting gene QKI‐5 .